Study of serum calcium and phosphorus levels in chronic kidney disease patients with acute coronary syndrome - Noher M. Abass; Ahmed. M. Yousef; Eman A. Sabet; Yasser M. Kamal; Mohamed H. El-Rashidy (SpringerOpen, 2024)
Abstract Background Cardiovascular (CVS) conditions remain the main etiology of death in individuals with chronic kidney disease (CKD) even after control of classic risk factors of cardiovascular disease (CVD). Aim This study is to detect the sequalae of serum phosphorus and calcium level abnormalities in individuals with CKD and their relation to occurrence of acute coronary syndrome (ACS) in those cases. Methods A cross-sectional work involved 100 individuals with CKD managed with or without dialysis. They were admitted to Internal Medicine Department, Coronary Care Unit of Sohag University Hospital. Each participant had been subjected to full history taking, clinical assessment, and investigations including serum calcium, phosphorus, creatinine, blood urea, parathyroid hormone level, lipid profile, troponin, CK-MB, electrocardiogram, and echocardiography. Results A substantial elevation in serum calcium and phosphorus levels was existed in individuals with CKD with ACS group compared to patients with CKD without ACS group (p = 0.026 and 0.001 respectively). The mean calcium/phosphorus ratio was 3.04 ± 2.14 in patients with CKD with ACS group, while it was 2.31 ± 1.17 in patients with CKD without ACS group. A substantial raise in calcium/phosphorus ratio was existed in CKD with ACS group as compared to patients with CKD without ACS group (p = 0.047). ROC curve analysis shows that calcium/phosphorus ratio can predict acute coronary syndrome at cutoff 1.94 with area under the curve 0.652 with sensitivity and specificity that were 77.8% and 52.1% correspondingly (p = 0.007). Conclusion A substantial raise in calcium and phosphorus levels was existed in individuals with CKD with ACS group contrasted to individuals with CKD without ACS group. Calcium/phosphorus ratio can predict acute coronary syndrome at cutoff 1.94. Clinical trial registration number NCT05134220.